Chemical Composition, Antioxidant, and Anti-inflammatory Activities of Whole Parts of Onobrychis crista-galli (L.) Lam - Benchadi, Wassila; Haba, Hamada; Queiroz, Emerson F.; Marcourt, Laurence; Wolfender, Jean-Luc; Bensouici, Chawki; Benkhaled, Mohammed (Natural Products Journal, The, 2020)
Objective: The aim of the present study is to examine the phytochemical components and the biological activities of the whole parts of Onobrychis crista-galli (L.) Lam. growing in Algeria. Methods: The structures of the isolated compounds 1-15 were elucidated using different spectroscopic methods and by comparison with literature data. The biological evaluation of the plant was determined by the in vitro antioxidant and anti-inflammatory activities. The antioxidant activity of various extracts (petroleum ether, ethyl acetate, and n-butanol) and some isolated flavonoids was assessed by using five different test systems, namely, 1,1-diphenyl-2-picryl-hydrazil (DPPH), 2,2’- azinobis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS), cupric reducing antioxidant capacity (CUPRAC), superoxide alkaline DMSO, and β-carotene/linoleic acid tests. In addition, the total phenolic and flavonoid contents of the extracts were determined as gallic acid and quercetin equivalents, respectively. In vitro anti-inflammatory activity by protein denaturation was measured for all extracts. Results: Phytochemical investigation of the ethyl acetate and n-butanol extracts of Onobrychis crista- galli led to the isolation for the first time of fifteen known compounds. The present study reports for the first time the isolation and identification of fifteen known compounds from this species. The ethyl acetate extract had rich phenolic content indicating (31.09 ± 0.40 mg gallic acid equivalents/g of fresh weight), while n-butanol extract displayed a high content in flavonoid compounds (60.70±0.7 mg quercetin equivalents/ g of fresh weight). This investigation indicated that the ethyl acetate extract of O. crista-galli showed the highest antioxidant activity (IC50= 17.13±0.51 μg/mL, DPPH), (IC50= 82.99±2.50 μg/mL, ABTS), and (A0.50= 94.67±0.41 μg/mL, CUPRAC), (IC50= 97.09±2.20 μg/mL, DMSO), (IC50: 36.73±1.17 μg/mL, β-carotene/linoleic acid). Furthermore, the compound luteolin 5-methyl ether (14) exhibited a good antioxidant activity in DPPH (IC50= 06.05 ± 0.15 μg /mL) and CUPRAC (A0.5= 12.57 ± 0.34 μg /mL) assays. Moreover, the ethyl acetate and nbutanol extracts of O. crista-galli evidenced a good to moderate in vitro anti-inflammatory activity. Conclusion: The extracts of the whole plant of O. crista-galli (L.) Lam. showed potent antioxidant and anti-inflammatory activities.
Keywords: anti-inflammatory activity